Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. Issue 3 (September 2017) - Wain, Louise V.; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J.; Erzurumluoglu, A. Mesut; O'Reilly, Paul F.; Cabrera, Claudia P.; Warren, Helen R.; Rose, Lynda M.; Verwoert, Germaine C.; Hottenga, Jouke-Jan; et al.
Abstract : Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project–based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near HSPB7, TNXB, LRP12, LOC283335, SEPT9, and AKT2, and provide new replication evidence for a further 2 signals in EBF2 and NFKBIA . Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation. Abstract : Supplemental Digital Content is available in the text.